2012
DOI: 10.1016/j.ijid.2012.05.171
|View full text |Cite
|
Sign up to set email alerts
|

Detection of lamivudine and adefovir resistance mutations among Filipino patients with chronic hepatitis B using line probe assay

Abstract: Background: Hepatitis B virus (HBV) mutations conveying resistance to antivirals are a major health concern worldwide in the treatment of chronic hepatitis B infection. The availability of a sensitive assay that can detect emerging HBV antiviral resistance mutations is important for individualized monitoring of response to standard of care treatment. The risk of developing lamivudine (LAM) resistance is 14% to 70% after 1 to 5 years of treatment, which is sufficiently high to justify HBV antiviral resistance m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Table 3 illustrates that the HBV genotype does not seem to have a substantial impact on the clinical manifestations of hepatitis B patients [ 65 ]. Numerous investigations have demonstrated that there is no meaningful correlation between HBV genomes and clinical characteristics such as liver histology, ALT levels, liver fibrosis, and HBeAg status [ 66 , 67 ]. Nonetheless, some research has indicated that a greater viral load may be linked to specific HBV genotypes [ 68 ].…”
Section: Prognostic Markersmentioning
confidence: 99%
“…Table 3 illustrates that the HBV genotype does not seem to have a substantial impact on the clinical manifestations of hepatitis B patients [ 65 ]. Numerous investigations have demonstrated that there is no meaningful correlation between HBV genomes and clinical characteristics such as liver histology, ALT levels, liver fibrosis, and HBeAg status [ 66 , 67 ]. Nonetheless, some research has indicated that a greater viral load may be linked to specific HBV genotypes [ 68 ].…”
Section: Prognostic Markersmentioning
confidence: 99%